Legal Disharmony and Disaster Risks: Ecological Sovereignty Restoration Through the Indigenous Peoples Bill - Ahmad Wasito (Pustaka Peradaban, 2025)
The escalation of hydrometeorological disasters in the upstream regions of Sumatra reflects a systemic failure in forestry governance, which is increasingly ensnared in an extractive paradigm. This article aims to analyze the correlation between regulatory disharmony and the rising risk of ecological disasters, while repositioning the Indigenous Peoples Bill as a preventive judicial instrument within the national disaster mitigation framework. Utilizing a normative legal research approach through a discourse analysis of sectoral regulations and policies, this study demonstrates that regulatory fragmentation—particularly following the implementation of the Job Creation Law—has precipitated an